Incidence of Pleural Effusion in Patients with Pulmonary Embolism - Liu, Min (Chin Med J (Engl), 2015)
BACKGROUND: No data on the incidence of pleural effusion (PE) in Chinese patients with pulmonary embolism are available to date. The aim of the current study was to investigate the frequency of PE in a Chinese population of patients with pulmonary embolism. METHODS: This was a retrospective observational single-center study. All data of computed tomography pulmonary angiography (CTPA) performed over 6-year period on adult patients with clinically suspected pulmonary embolism were analyzed. RESULTS: From January 2008 until December 2013, PE was identified in 423 of 3141 patients (13.5%) with clinically suspected pulmonary embolism who underwent CTPA. The incidence of PE in patients with pulmonary embolism (19.9%) was significantly higher than in those without embolism (9.4%) (P < 0.001). Majority of PEs in pulmonary embolism patients were small to moderate and were unilateral. The locations of emboli and the numbers of arteries involved, CT pulmonary obstruction index, and parenchymal abnormalities at CT were not associated with the development of PE. CONCLUSIONS: PEs are present in about one fifth of a Chinese population of patients with pulmonary embolism, which are usually small, unilateral, and unsuitable for diagnostic thoracentesis.